Upaya Meningkatkan Kompetensi Pedagogik Guru Melalui Pemberian Penghargaan Di SDN 005 Rokan IV Koto - Masrul Masrul (JURNAL PENDIDIKAN ROKANIA, 2018)
This study aims to determine whether the Pedagogical Competencies of Teachers can be improved by Granting Award at SDN 005 Rokan IV Koto. The School Action Research was conducted only at SDN 005 Rokan IV Koto. In one supervision of the researcher himself. This was chosen because it was very supportive of the Principal's job to know the pedagogic teacher's competencies. This study was conducted in two cycles. From the description of data processing and discussion it can be concluded that teacher pedagogic competence is obtained in cycle I of 65% with good category and in cycle II increased to 86% with very good category